2008
DOI: 10.7863/jum.2008.27.1.125
|View full text |Cite
|
Sign up to set email alerts
|

Imaging Findings of Chest Wall Lesions on Breast Sonography

Abstract: Objective. The purpose of this presentation is to illustrate the sonographic findings of chest wall lesions that were depicted on breast sonography. Methods. Chest wall lesions detected during breast sonography were collected and reviewed retrospectively. Results. The sonographic findings of normal chest walls and various pathologic chest wall lesions, including inflammatory lesions, benign neoplasms, and malignant neoplasms, are discussed. Conclusions. Familiarity with normal sonographic anatomy and chest wal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 35 publications
0
31
0
Order By: Relevance
“…It was located in the premammary zone, not in the mammary fibroglandular zone which is the common layer for developing breast cancer. A mass in the subcutaneous fat layer suggests the possibility of various neoplasms, such as metastatic tumors, hemangioma, neurogenic tumor, and soft tissue sarcoma, rather than tumors of fibroglandular origin such as fibroadenoma or recurring breast cancer [12]. Since breast sarcomas have no specific radiological features that can be differentiated from benign tumors, we should expand the list of differential Definitive diagnosis can be made by surgical biopsy and immunohistochemical studies, because fine-needle aspiration biopsy and core-needle biopsy are reported to underdiagnose the tumors [2,6,11].…”
Section: Accepted Manuscriptmentioning
confidence: 98%
“…It was located in the premammary zone, not in the mammary fibroglandular zone which is the common layer for developing breast cancer. A mass in the subcutaneous fat layer suggests the possibility of various neoplasms, such as metastatic tumors, hemangioma, neurogenic tumor, and soft tissue sarcoma, rather than tumors of fibroglandular origin such as fibroadenoma or recurring breast cancer [12]. Since breast sarcomas have no specific radiological features that can be differentiated from benign tumors, we should expand the list of differential Definitive diagnosis can be made by surgical biopsy and immunohistochemical studies, because fine-needle aspiration biopsy and core-needle biopsy are reported to underdiagnose the tumors [2,6,11].…”
Section: Accepted Manuscriptmentioning
confidence: 98%
“…The chest wall consists of four layers: the skin, subcutaneous fat, superficial muscles, and the ribs and intercostal muscles . The skin appears sonographically as a thin hyperechoic layer.…”
Section: Chest‐wall Anatomymentioning
confidence: 99%
“…A retromammary fat layer is located between the breast parenchyma and the pectoral muscle. Lesions originating from the chest wall displace this retromammary fat layer superficially …”
Section: Chest‐wall Anatomymentioning
confidence: 99%
See 2 more Smart Citations